PENGARUH ADITIF EM4 (effective microorganism), AIR TEBU DAN TEPUNG JAGUNG TERHADAP KUALITAS UJI ORGANOLEPTIK SILASE RUMPUT KUMPAI (Hymenachine amplexicaulis) - Kastalani Kastalani; Maria Erviana Kusuma; Desty Laurena (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
The study aims to determine the effect of various EM4 (effective microorganism) mixtures, sugarcane juices and corn flour on the physical quality of silage of Kumpai Grass (Hymenachine amplexicaulis).  To get the right level of additive mixture to produce good  dilation This research was conducted using a randomized complete design with treatment A (EM3 3%, Sugarcane water 1%, Corn flour 2%), B (EM3 3%, Sugarcane water 2%, Corn flour 3%),  A (EM3 3%, Sugarcane water 3%, Corn flour 6%),   A (EM3 3%, Sugarcane water 4%, Corn flour 8%). The observed variables were physical silage in the form of odor, texture and color.  The result showed that the addition of EM4 (effective microorganism) additives, sugarcane juices and corn flour had no effect on organoleptic testing of silage Kumpai Grass (Hymenachine amplexicaulis).